Real communication : how to be you and lead true - Dolan, Gabrielle (Recorded Books, Inc., 2019)
What's happened to real? In a world of jargon, acronyms and distrust, does authenticity in leadership mean anything anymore? The answer is a resounding YES. As the expectations of customers and employees evolve at a breakneck pace, businesses and organisations are starving for real communication and authentic leadership. But there's a lot of baggage and distrust to overcome. Real Communication shows you how decades of systematic deceit, jargon, alternative facts and a top-down culture of self-protection have nurtured cynicism in our organisations. With real-life case studies, pointers and guidelines, leadership consultant Gabrielle Dolan shows you how authenticity can earn trust with honest communication, and why it's well worth the effort. Great leadership demands commitment. Are you ready to get real? Learn how to:communicate more effectivelyimprove employee engagementhelp your team cope with changelead significant organisational transformationmanage the new generation of employeesWhen trust is broken, it is extremely hard to rebuild. Real Communication shows you how to do it, and the payoff is priceless.